The structural basis of aldo-keto reductase 1C3 inhibition by 17α-picolyl and 17(E)-picolinylidene androstane derivatives - Plavša-Puž, Jovana J; Brynda, Jiří; Ajduković, Jovana J; Bekić, Sofija; Ćelić, Andjelka; Řezáčová, Pavlína; Škerlová, Jana; Petri, Edward (Journal of enzyme inhibition and medicinal chemistry, 2025)
Human aldo-keto reductase 1C3 (AKR1C3) is a steroid modifying enzyme involved in cancer progression. Here, A-ring modified 17α-picolyl and 17(E)-picolinylidene androstane derivatives are shown to inhibit AKR1C3 activity in vitro. None of the androstane derivatives have off-target affinity for the androgen receptor, based on a fluorescence assay in yeast cells. The X-ray structure of AKR1C3 in complex with the strongest inhibitor, a 17α-picolyl androstane with a C3-oxime modification, was determined at 1.7 Å resolution. Based on this crystal structure and molecular docking, inhibition of AKR1C3 by the 17α-picolyl or 17(E)-picolinylidene derivatives depends on interactions between the C3 modification and the NADP+ cofactor, while the C17α-picolyl or C17-picolinylidene group anchors the inhibitor to AKR1C3. Because one AKR1C3 inhibitor identified here was also previously reported to inhibit CYP17, it may be possible for future researchers to design dual AKR1C3/CYP17 inhibitors based on a steroid scaffold for potential treatment of advanced prostate cancers.
Keywords: CYP17; krystalografie rentgenová; protein X-ray crystallography; Structure-Activity Relationship; protein AKR1C3; molekulární struktura; Molecular Structure; vztah mezi dávkou a účinkem léčiva; Enzyme Inhibitors; Molecular Docking Simulation; molecular docking; AKR1C3; Crystallography, X-Ray; vztahy mezi strukturou a aktivitou; prostate cancer; simulace molekulového dockingu; lidé; Humans; androstany; Aldo-Keto Reductase Family 1 Member C3; Androstanes; Dose-Response Relationship, Drug; inhibitory enzymů